Virion encapsidated HIV-1 Vpr induces NFAT to prime non-activated T cells for productive infection. Issue 7 (July 2016) - Höhne, Kristin; Businger, Ramona; van Nuffel, Anouk; Bolduan, Sebastian; Koppensteiner, Herwig; Baeyens, Ann; Vermeire, Jolien; Malatinkova, Eva; Verhasselt, Bruno; Schindler, Michael
Abstract : The majority of T cells encountered by HIV-1 are non-activated and do not readily allow productive infection. HIV-1 Vpr is highly abundant in progeny virions, and induces signalling and HIV-1 LTR transcription. We hence hypothesized that Vpr might be a determinant of non-activated T-cell infection. Virion-delivered Vpr activated nuclear factor of activated T cells (NFAT) through Ca 2+ influx and interference with the NFAT export kinase GSK3β. This leads to NFAT translocation and accumulation within the nucleus and was required for productive infection of unstimulated primary CD4 + T cells. A mutagenesis approach revealed correlation of Vpr-mediated NFAT activation with its ability to enhance LTR transcription and mediate cell cycle arrest. Upon NFAT inhibition, Vpr did not augment resting T-cell infection, and showed reduced G2/M arrest and LTR transactivation. Altogether, Vpr renders unstimulated T cells more permissive for productive HIV-1 infection and stimulates activation of productively infected as well as virus-exposed T cells. Therefore, it could be involved in the establishment and reactivation of HIV-1 from viral reservoirs and might have an impact on the levels of immune activation, which are determinants of HIV-1 pathogenesis.